Investigating youth perceptions of youth participation in development: a focus on community engagement as a platform for youth/student participation at Rhodes University - Dano, Nqaba (Rhodes University, Faculty of Humanities, Department of Sociology, 2016)
The main objective of the study is to investigate youth perceptions of youth participation in development with a focus on the Rhodes Community Engagement programme as a platform for youth participation. The study was inspired by trying to locate the position that youth put themselves in when they regard their own participation in development. It was further motivated by trying to gain perspectives from the youth themselves because most discourses on youth rarely feature their own voices. The study utilized a qualitative methodology with an interpretive paradigm, which used semi-structured in-depth interviews as a method of data collection. The theoretical framework used was the notion of participatory development. The literature consulted was broken up into participation in development which looked at the history of participation and the need for participation, the importance of participation and the limits of participation and the type of participation. It looked at youth participation, the definition of youth as a group in society and the discourses that surround how youth are defined; lastly it looked at community engage in higher education, the role students place in community engagement and the nature of Rhodes Community engagement. The data was discussed and analysed following the above mentioned themes which were participation in development, youth participation and community engagement. From the data collected it was made evident that if youth are given more spaces and chances to actively participate they could challenge prominent discourses that treat them as irresponsible minors and exclude them from decision-making processes that directly affect them and the society within which they live.
Keywords: Uncatalogued